Differential scanning calorimetry for quantification of polymer biodegradability in compost. (April 2020) - Capitain, Charlotte; Ross-Jones, Jesse; Möhring, Sophie; Tippkötter, Nils
Abstract: The objective of this study is the establishment of a differential scanning calorimetry (DSC) based method for online analysis of the biodegradation of polymers in complex environments. Structural changes during biodegradation, such as an increase in brittleness or crystallinity, can be detected by carefully observing characteristic changes in DSC profiles. Until now, DSC profiles have not been used to draw quantitative conclusions about biodegradation. A new method is presented for quantifying the biodegradation using DSC data, whereby the results were validated using two reference methods. The proposed method is applied to evaluate the biodegradation of three polymeric biomaterials: polyhydroxybutyrate (PHB), cellulose acetate (CA) and Organosolv lignin. The method is suitable for the precise quantification of the biodegradability of PHB. For CA and lignin, conclusions regarding their biodegradation can be drawn with lower resolutions. The proposed method is also able to quantify the biodegradation of blends or composite materials, which differentiates it from commonly used degradation detection methods. Graphical abstract: Image 1 Highlights: A method for analysis of the degradation of polymers in a complex environment is established using DSC. Structural changes during biodegradation, such as an increase in brittleness or crystallinity, can be detected. Biodegradation is quantified with minimal sample preprocessing and small sample volumes. Biodegradation of three polymeric biomaterials, polyhydroxybutyrate, cellulose acetate and lignin, is evaluated.